A Survey of Parallel Message Authentication and Hashing Methods (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:Currently, there are approximately 4.95 billion people who use the Internet. This massive audience desires internet shopping, information exchange, social networking, and other activities that have grown dramatically in recent years. Therefore, it creates the need for greater confidentiality and privacy. In recent days, fraud via the Internet has been one of the key impediments to the dissemination of the use of business apps. Therefore, the three important security concerns actually occur daily in our world of transparent fashion, more accurately: identity, authentication, and authorization. Identification is a procedure that permits the recognition of an entity, which may be a person, a computer, or another asset such as a software programmer.Materials and Methods:In security systems, authentication and authorization are two complementary procedures for deciding who may access the information resources across a network. Many solutions have been presented in the literature. To get more performance on the authentication algorithmic, researchers used parallelism to increase the throughput of their algorithms.  On the one hand, various approaches have been employed to enhance the security of cryptographic systems, including increasing the number of rounds, utilizing substitution tables, and integrating other security primitives for encryption and message authentication.Results:Recent studies on parallel message authentication and hashing algorithms have demonstrated that GPUs outperform other parallel platforms in terms of performance.Conclusion:This work presents a parallel implementation of message authentication techniques on several platforms. It is studying and demonstrating works which discuss authentication, hashing, and their implementation on a parallel platform as a main objective.